The politics of the Italian Renaissance State: Italian scholarship for non-Italians - Napolitano, David (Incontri. Rivista europea di studi italiani, 2014)
Review of: The Italian Renaissance State, A. Gamberini & I. Lazzarini (eds), Cambridge, Cambridge University Press, 2012, 634 p., ISBN: 9781107010123, € 100,00.